2008
DOI: 10.1590/s0100-40422008000500033
|View full text |Cite
|
Sign up to set email alerts
|

Determinação espectrofotométrica de citrato de sildenafil em formulações farmacêuticas

Abstract: Recebido em 25/5/07; aceito em 11/10/07; publicado na web em 2/4/08 SPECTROPHOTOMETRIC DETERMINATION OF SILDENAFIL CITRATE IN PHARMACEUTICAL FORMULATIONS. This paper describes a simple and rapid spectrophotometric method for quantitative determination of sildenafil citrate based on its reaction with p-chloranil accelerated by hydrogen peroxide, producing a stable purple compound (λ max = 535 nm). In the absence of peroxide this reaction is very slow. The experimental conditions were optimized by using response… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0
10

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 23 publications
(28 reference statements)
0
6
0
10
Order By: Relevance
“…Além disso, esses métodos cromatográficos utilizam solventes orgânicos na composição da fase móvel, gerando grandes quantidades de resíduos tóxicos. Neste sentido, na literatura são descritos outros métodos que buscam contornar esses problemas para determinação de CS em medicamentos, como por exemplo, utilizando a eletroforese capilar 9 , espectrofotometria UV-VIS, [10][11][12][13][14][15] dispersão de Rayleigh 16 e, em destaque, o eletroanalítico devido à sua alta sensibilidade, seletividade e baixo custo de instrumentação. [17][18][19][20][21][22][23][24][25][26][27][28] Dentre esses métodos eletroanalíticos para a determinação de CS, as técnicas voltamétricas de pulso diferencial e onda quadrada são as mais aplicadas usando diversos eletrodos de trabalho, como por exemplo: gota pendente de mercúrio, 17 filme de bismuto, 18 filme de chumbo, 19 carbono vítreo, 20, 21 pasta de diamante, 22 pasta de carbono modificada, 23 carbono vítreo modificado com óxido de grafeno, 24 diamante dopado com boro (BDD, Boron-Doped Diamond) 25 e eletrodos impressos (SPE, Screen-Printed Electrode).…”
Section: Introductionunclassified
See 1 more Smart Citation
“…Além disso, esses métodos cromatográficos utilizam solventes orgânicos na composição da fase móvel, gerando grandes quantidades de resíduos tóxicos. Neste sentido, na literatura são descritos outros métodos que buscam contornar esses problemas para determinação de CS em medicamentos, como por exemplo, utilizando a eletroforese capilar 9 , espectrofotometria UV-VIS, [10][11][12][13][14][15] dispersão de Rayleigh 16 e, em destaque, o eletroanalítico devido à sua alta sensibilidade, seletividade e baixo custo de instrumentação. [17][18][19][20][21][22][23][24][25][26][27][28] Dentre esses métodos eletroanalíticos para a determinação de CS, as técnicas voltamétricas de pulso diferencial e onda quadrada são as mais aplicadas usando diversos eletrodos de trabalho, como por exemplo: gota pendente de mercúrio, 17 filme de bismuto, 18 filme de chumbo, 19 carbono vítreo, 20, 21 pasta de diamante, 22 pasta de carbono modificada, 23 carbono vítreo modificado com óxido de grafeno, 24 diamante dopado com boro (BDD, Boron-Doped Diamond) 25 e eletrodos impressos (SPE, Screen-Printed Electrode).…”
Section: Introductionunclassified
“…Além disso, esses métodos cromatográficos utilizam solventes orgânicos na composição da fase móvel, gerando grandes quantidades de resíduos tóxicos. Neste sentido, na literatura são descritos outros métodos que buscam contornar esses problemas para determinação de CS em medicamentos, como por exemplo, utilizando a eletroforese capilar 9 , espectrofotometria UV-VIS, [10][11][12][13][14][15] dispersão de Rayleigh 16 e, em destaque, o eletroanalítico devido à sua alta sensibilidade, seletividade e baixo custo de instrumentação. …”
unclassified
“…Methods based on the formation of colored complexes for the determination of SILC in tablets have also been described by visible spectrophotometry (Amin, ElBeshbeshy, 2001;Dinesh et al, 2002;Salem, 2006;Weinert, Pezza, Pezza, 2008;Issa et al, 2010;Frag, Mohamed, Alelaiwe, 2011a). Spectrofluorimetry and electroanalytical methods such as voltammetry using different electrodes were exploited by several researchers (Othman, Rizk, El-Shahawi, 2004;Hassan et al, 2006;Tyszczuk, Korolczuk, 2010;Wang et al, 2010;Balasoiu et al, 2011;Frag, Mohamed, Alelaiwe, 2011b;Wang, Gómez, Fernandez, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…These tools enable relevant inferences from a reduced experiment and consider the effects of interactions between factors (Aznar and Maduro, 2008). This is important, as it was experimentally observed that level change to a factor can alter other responses with synergistic or antagonistic effect, which it was not possible to assess with univariate studies (Weinert et al, 2008;Breitkreitz et al, 2014). Therefore, factorial design has been used in a diversified way such as in the analysis of metals (Pereira Filho et al, 2002), plants (Marques et al, 2012;Souza and Sena, 2012), and soils (Dolatto et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, factorial design has been used in a diversified way such as in the analysis of metals (Pereira Filho et al, 2002), plants (Marques et al, 2012;Souza and Sena, 2012), and soils (Dolatto et al, 2012). Although there are few results of response surface application, using this tool, it was possible to find the optimum conditions for: (i) extrusion of soybean bran (Barros et al, 1987), (ii) spectrophotometric determination in pharmaceutical formulations (Weinert et al, 2008), and (iii) fruit productivity and quality because of the use of fertilizers (Mattos et al, 2004).…”
Section: Introductionmentioning
confidence: 99%